The significance of strategic Human Resource Management practiced in HR consultancy firms in Bangladesh to ensure proper organizational growth - Hossain, Md. Rabaid (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2015.